Menggugat Khilafah: Reaktualisasi Pemikiran Politik Ali Abdul Raziq - Syahir, Ahmad; Hasan, Ahmadi; Umar, Masyithah; Khasyi'in, Nuril (Interdisciplinary Explorations in Research Journal, 2024)
Abstract Among Islamic thinkers, the relationship between Islam and the state is still a matter of debate which has implications for the birth of typologies, namely integralistic, symbiotic, and secularistic. The three paradigms of the relationship have the same goal, namely finding reconciliation between religious ideality and political reality, which is the main task of Islamic political thinkers. Ali Abdul Raziq as one of the Islamic thinkers, also colored the debate, even arguably became a trendsetter, especially his thoughts on the khilafah. This paper raises Raziq's thoughts on the khilafah, one of whose goals is to actualize it in the midst of the unfinished debate of Islamic intellectuals. The results of the study show that the khilafah is seen as having no basis in the Qur'an, Sunnah, or Ijma'. Islam is seen as not demanding its people to determine the type or form of government, this is more appropriate to be left to the people based on logic and experience. Keywords: khilafah, paragidma, fundamental, moderate, liberal. Abstrak Di kalangan pemikir Islam, hubungan Islam dan negara masih menjadi perdebatan yang berimplikasi pada lahirnya tipologi, yaitu intgralistik, simbiotik, dan sekularistik. Ketiga paradigma hubungan tersebut memiliki tujuan yang sama, yaitu menemukan rekonsiliasi antara idealitas agama dan realitas politik yang menjadi tugas utama para pemikir politik Islam. Ali Abdul Raziq sebagai salah satu pemikir Islam, turut mewarnai perdebatan tersebut, bahkan dapat dibilang menjadi trendsetter, khususnya pemikirannya tentang khilafah. Tulisan ini mengangkat pemikiran Raziq tentang khilafah yang salah satu tujuannya adalah untuk mengaktualisasi ke tengah-tengah perdebatan para intelektual Islam yang belum tuntas. Dari hasil kajian menunjukkan bahwa khilafah dipandang tidak memiliki landasan dalil di dalam al-Qur’an, Sunnah, maupun Ijma’. Islam dipandang tidak menuntut umatnya untuk menentukan jenis atau bentuk pemerintahan, hal ini lebih tepat diserahkan kepada umat berdasarkan logika dan pengalamannya. Kata Kunci: khilafah, paragidma, fundamental, moderat, liberal.